Inorganic Polymers From CaO-FeOx-SiO2 Slag: The Start of Oxidation of Fe and the Formation of a Mixed Valence Binder - Peys, Arne; Douvalis, Alexios P.; Hallet, Vincent; Rahier, Hubert; Blanpain, Bart; Pontikes, Yiannis (Frontiers in Materials, 2019)
Belonging to the family of alternative cementitious materials, inorganic polymers are rising in importance because of the drive to decrease CO2 emissions of concrete production. A synthetic Fe-rich slag resembling industrial copper or lead slags, was mixed with a sodium silicate activating solution. 57Fe Mössbauer spectra analyses indicate that the oxidation reactions are taking place simultaneously with the polymerization reactions. The slag contains Fe2+ states and a small amount of Fe3+. During polymerization a new octahedral Fe2+ state is formed, while oxidation is manifested through the appearance of an additional Fe3+ state. The reactions continue after setting, lowering the relative contributions of the slag in the Mössbauer and FTIR spectra of the samples. The Na+/Fe3+ molar ratio in the mixture that makes up the binder after 28 days is approximately 1, suggesting the participation of tetrahedral Fe3+ in the silicate framework, charge balanced by Na+.